Zakat Fund As The Starting Point Of Entrepreneurship In Order to Alleviate Poverty (SDGs Issue) - Lily Rahmawati Harahap (Global Review of Islamic Economics and Business, 2018)
As known, Indonesia is a nation with the largerst Moslem society in the world. According to data issued by Bappenas, in 2020 the population of Indonesia is predicted about 271,066,400 people (Bappenas: 2018). 85 percent of this population (ca. 230.406.440 people) are Moslems. It shows the huge potential in the acceptance of zakat fund, as an obligation for a Moslem who has qualified in accordance with the provisions of Islam.            Since MDGs declared in 2000 (UNRC: 2008) which contains a commitment to accelerate human development and poverty alleviation (8 goals),  Indonesia has a strong commitment to achieve the MDGs targets became one of Indonesia’s main priorities. As a continuation of the MDGs program, in 2015, more than 190 world leaders committed to 17 Sustainable Development Goals (SDGs). In Indonesia, 17 SDGs are grouped into 4 part, one of them is poverty alleviation (UNDP Indonesia: 2018). One of the goals for poverty alleviation is explained with the goal number 8, that is decent work and economic growth. And one of the drivers the existence of decent work and economic growth is the growth of entrepreneurship activities.The growth of entrepreneurship can be implemented with the support of funds. One of them come from the distribution of zakat fund acceptance.            By terminology, zakat means a certain amount of property that is required by Allah SWT to be given to the mustahik mentioned in the Qur’an. Or it could also mean a certain amount of certain property given to a particular person (Solihin: 2010). There is a fund transfer from muzaki (zakat payer) to mustahik (zakat recipient).With the transfer of funds, there is an expectation that there will be a better life change for mustahik, so that in time they will be becomes muzaki.This activity is expected to occur continously, forming a circle of increasing goodness. And ultimately will improve society wellbeing.            To support this paper, the author use a qualitative methods with secondary datas and supported by Tawhidi String Relation (TSR) theory which includes the method of circular causation and IIE (interaction, integration and evolution) method. Keywords : zakat, entrepreneurship, poverty alleviation, SDGs, TSR